New species of the non-biting midges of Tribe Chironomini (Dptera, Chironomidae) from the Bolshekhekhtsyrsky Reserve (Russia, Khabarovsk Territory) - Orel, Oksana V. (Zootaxa, 2018)
Three new species of non-biting midges of the tribe Chironomini, Polypedilum (s. str.) odyrensis sp.n., Polypedilum (s. str.) servatum sp.n., Robackia lukini sp.n., are described on the morphology of imago males collected on the streams of the Bolshekhekhtsyrsky Nature.